PENGAWASAN DAN PENILAIAN UJI KOMPETENSI SEKOLAH MENENGAH KEJURUAN (SMK) KOMPETENSI KEAHLIAN TEKNIK KOMPUTER DAN JARINGAN SMK N I MARTAPURA OGAN KOMERING ULU TIMUR - Defi Pujianto (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2021)
SMK is a secondary school that emphasizes skills. Students are provided with skills acquired from school as well as skills acquired during practice. The Skills Competency Examination aims to measure the achievement of student competencies at a certain level according to the Expertise Competencies taken in SMK. The role of Competency Test Assessors consists of a combination of internal and external examiners. Internal Examiners are productive teachers who are relevant to the field. External examiners come from DUDI / professional associations / partner institutions who have educational backgrounds or work experience relevant to the Expertise Competencies to be tested. As in the previous year, UKK scores will be calculated as School Exam Scores for vocational competency subjects. In general, the UKK device consists of, Vocational Practice Questions (SPK) in the form of assignments for test participants, and Practice Question Assessment Guidelines (PPSP) are instruments used for scoring each component of the assessment. The assessment sheet contains assessment components, assessment sub-components, competency achievement, and assessment criteria/rubrics. w:LsdException Locked="false" Priority="46" Name="Grid Table 1 Light Acce